Environmental Accounting Practices and Corporate Sustainability Performance Measurement (gjstudies, 2020)
This research introduces a novel methodological framework that integrates environmental accounting practices with corporate sustainability performance measurementthrough a bio-inspired computational approach. Traditional sustainability metricshave largely relied on standardized reporting frameworks that often fail to capturethe complex, dynamic interactions between environmental expenditures and long-termcorporate sustainability outcomes. Our study addresses this gap by developing a hybrid methodology that combines ecological network analysis with machine learningtechniques to model corporate environmental systems as adaptive biological ecosystems. We propose that environmental accounting data—traditionally treated as discrete financial entries—can be reconceptualized as flows within a corporate metabolicnetwork, enabling the identification of critical leverage points for sustainability enhancement. The methodology employs a modified ant colony optimization algorithmto trace resource flows through corporate environmental systems, identifying patternsof efficiency and waste that conventional accounting methods overlook. We apply thisframework to a longitudinal dataset spanning 150 multinational corporations across fiveindustries over a ten-year period. Our results demonstrate that companies exhibitinghigher network resilience and metabolic efficiency in their environmental accountingflows achieve significantly better sustainability performance across multiple dimensions, including reduced carbon intensity, improved resource circularity, and enhancedstakeholder trust. The findings reveal three distinct corporate environmental metabolicarchetypes—linear, transitional, and circular—each with characteristic accounting flowpatterns and sustainability outcomes. This research contributes to both accountingand sustainability literature by providing a dynamic, systems-based approach to environmental performance measurement that transcends traditional compliance-focusedmetrics and offers actionable insights for strategic environmental management. Theproposed framework enables organizations to move beyond static sustainability reporting toward adaptive environmental governance informed by real-time accounting dataflows